Time management, self-esteem & academic performance of international students from Iraq in Universiti Putra Malaysia - Falah, Dhubyan Jihad; Yusof, Aminuddin (INSInet Publications, 2016)
Background: Time management, test competence, academic competence, and study techniques are some of the factors that affect an individuals' academic performance(Sansgiry et al.,2006). The relationship between self achievement has been highlighted in the literature (Harris,2009; Mohammad, 2010; Sadaat, Ghasemzadeh & Soleimani, 2012; Rosli,et al., 2011). However, no studies addressed how self-esteem and time management combine to predict academic success. Objective:This study examines the relationship between time management,self-esteem and academic performance of Iraqi graduate students studying in Universiti Putra Malaysia. Method: Data on time management and self esteem were collected from 169 subjects using instruments developed by Griffin & Van Fleet, (2013) and Results showed that majority of subjects (74.1%) had good time management skills and moderate level of self-esteem (77.7%).In terms of the relationship between time management and GPA, the results report no 0.03,p=0.698).Also there is no significant relationship Conclusion: This study showed there were no significant relationship between academic performance and time esteem of Iraqi students studying in Malaysia.The results also showed majority of students studying in Malaysia had very good and excellent results (GPA above 3.30). For the small number of Iraqis with poor academic results, esteem and time management skills which could act as barriers to students attaining and maintaining a high GPA.